PENGARUH PERENDAMAN NACL DAN NAOH PADA PEMBUATAN KOMPOSIT SERAT PINANG DENGAN METODE VACCUM BAGGING - septio Novanto; Sehono; Ferry Setiawan (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
Composites are widely used in household appliances, as well as in the industrial sector. This is because composites have several advantages such as composite materials are stronger, more flexible and also resistant to corrosion. At this time betel nut is already used in the medical and cosmetic fields. However, the consequences of this processing still leave waste in the form of betel nut fiber. Such potential can be used as fibers in the manufacture of composites. The manufacture of composites this time uses lycal resin as a matrix and uses the vaccum bagging method. This study aims to determine the technical analysis and mechanical properties of making betel nut fiber composites to obtain tensile and bending strength results. The tensile test refers to ASTM D-638 and the bending test refers to ASTM D 790. In the NaCl immersion variation, the highest tensile value was obtained, namely 21.78 MPa, and in the NaOH immersion variation, the highest tensile value was obtained, which was 30.21 MPa. in the bending test the Immersion variation NaCl got the highest bending strength value with a value of 509.58 MPa and for the immersion variation NaOH got the highest bending strength value with a value of 555.82 MPa